Incidence Of Feline HaemotropicMycoplasmosis In Chennai, Tamil Nadu - Rajat Sagare; B Gowri; N R Senthil; K Jeyaraja; A Arunprasad (The Indian Veterinary Journal, 2025)
The present study was conducted at Madras Veterinary College Teaching Hospital to report the prevalence of feline infectious anemia. The diagnosis was confirmed by the presence of pleomorphic parasites at the marginal parts of erythrocytes in stained blood smear examination and PCR. Detailed clinical examination was done for all the suspected cats. Among thirty-seven cats screened, 2 animals were found positive for haemotropic mycoplasma organisms by blood smear examination. The blood samples were further subjected to DNA extraction followed by Polymerase Chain Reaction for confirmation of Haemoplasmosis with a positivity of 5 animals. The highest rate ofinfectionwasnoticedincatsofonetotwoyearsofagegroupwith40.00per cent while 3 among 5 cats were non-descript cats. Male cats were high incidence with 60.00 percent. Young male non-descript cats are more susceptible for feline mycoplasmosis.